Milo the Mouse : a use-your-words feeling book (A Use Your Words Feeling Book, 2013)
Children's feelings and emotions are strong, but smaller children can feel helpless without the ability to identify or articulate many of these feelings. Use-Your-Words Feeling Books feature storylines that help build emotional language skills, complete with interactive facial expressions to enhance children's understanding of others' emotions.